2015
DOI: 10.1039/c5nr01820j
|View full text |Cite
|
Sign up to set email alerts
|

Thiols as interfacial modifiers to enhance the performance and stability of perovskite solar cells

Abstract: Modifying the interfaces of CH3NH3PbI3 with TiO2 and hole transport layers using two different types of thiols leads to enhanced performance and stability of perovskite solar cells. The incorporation of HOOC-Ph-SH at the TiO2/perovskite interface facilitates electron transfer from perovskite to TiO2 and also alters the morphology of perovskite crystal growth to increase the power conversion efficiency. The modification of pentafluorobenzenethiol at the perovskite/hole transport layer interface improves the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
157
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(161 citation statements)
references
References 31 publications
4
157
0
Order By: Relevance
“…While the control device almost did not work after 12 h exposure to light, with TiO 2 /Sb 2 S 3 as ETL, PCE still maintained 65% of the initial value after the 12 h. This result again confirmed that UV‐induced reaction at the TiO 2 /CH 3 NH 3 PbI 3 interface was partly responsible for the degradation of the perovskite 113. In addition, other efficient modifiers have also been reported, including carboxylic acid–thiol ligands (HOOC—Ph—SH),114 fullerene derivatives PCBDAN,115 ionic‐liquid,116 LiSPS,117 cesium chloride,118 and polyoxyethylene 119…”
Section: Device Structurementioning
confidence: 99%
“…While the control device almost did not work after 12 h exposure to light, with TiO 2 /Sb 2 S 3 as ETL, PCE still maintained 65% of the initial value after the 12 h. This result again confirmed that UV‐induced reaction at the TiO 2 /CH 3 NH 3 PbI 3 interface was partly responsible for the degradation of the perovskite 113. In addition, other efficient modifiers have also been reported, including carboxylic acid–thiol ligands (HOOC—Ph—SH),114 fullerene derivatives PCBDAN,115 ionic‐liquid,116 LiSPS,117 cesium chloride,118 and polyoxyethylene 119…”
Section: Device Structurementioning
confidence: 99%
“…Pentafluorobenzenethiol, for example, was shown to increase the device durability at a relative humidity of 45%. 53 Modifying the perovskite surface with dodecyltrimethoxysilane (C 12 -silane), the devices lost merely 15% of their initial efficiency after 600 h under ambient conditions. 54 The main objective of many barrier layers is to hamper any moisture diffusion through the hole-transporter to prevent degradation.…”
mentioning
confidence: 99%
“…This increase of the efficiency was explained by the retardation of charge recombination, and better perovskite crystal growth. Some other organic monolayers were used to modify the surface of scaffold through the influence of the morphology and growth of perovskite, such as glycine, thiols and 4-aminobenzoic acid, yielding positive effects on cell performance [75][76][77]. A summary of the published representative results of MPSCs' performance parameters with different scaffold interface modification is listed in Table 2.…”
Section: Scaffold Interface Engineeringmentioning
confidence: 99%